1974
DOI: 10.1037/h0036677
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control in university students from Eastern and Western societies.

Abstract: Male and female students in Eastern, Western, and Middle-Eastern societies were given the Rotter Internal-External Locus of Control (I-E) Scale. Data from eight countries (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
3

Year Published

1977
1977
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 12 publications
4
32
3
Order By: Relevance
“…(Decimal commas omitted) required), and only a qualitative interpretation of the profiles in Table 4 is attempted. Firstly, it can be observed that there are distinct differences between groups as shown by the dispersion of mean externality scores (standard deviations) between situation types, and those from the present study are generally higher than those calculated from Parsons and Schneider (1974). If this is taken as a crude index of the degree to which there is differentiation between item types or separation of items into independent scales, then the typology works at least as well for the groups from Africa as for other groups; further multivariate or item analysis would have to be undertaken to substantiate this point.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…(Decimal commas omitted) required), and only a qualitative interpretation of the profiles in Table 4 is attempted. Firstly, it can be observed that there are distinct differences between groups as shown by the dispersion of mean externality scores (standard deviations) between situation types, and those from the present study are generally higher than those calculated from Parsons and Schneider (1974). If this is taken as a crude index of the degree to which there is differentiation between item types or separation of items into independent scales, then the typology works at least as well for the groups from Africa as for other groups; further multivariate or item analysis would have to be undertaken to substantiate this point.…”
Section: Resultscontrasting
confidence: 54%
“…As a validity check, the logically derived item typology of Schneider and Parsons (1970) and Parsons and Schneider (1974) was applied to the data. Table 4 gives the mean externality proportion for each type of item, corrected for overall group differences by reduction to a mean of 0,500.…”
Section: Resultsmentioning
confidence: 99%
“…When individuals do not feel responsible for their success and failures, and then are deviant from what is called the norm of internality (Beauvois, 1984;Jellison & Green, 1981), they have two external possible ways of escaping this norm: Either they invoke the random world (chance, luck), or they invoke the impact of a politicoreligious force (where destiny and other all-powerful agents predominate). Whenever differences between cultures in internality scores have been observed (Parsons & Schneider, 1974), it is still necessary to verify whether the norm of internality implies the same referents and whether externality refers to the same explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Munro (1979) compared the attribution of causality in black and white students in Zambia and Zimbabwe-Rhodesia utilizing a multifactorial model of locus of control. Parsons and Schneider (1974) studied locus of control in male and female students in eastern, middle eastern, and western societies. Results indicated that Japanese students were more external than students from other countries, and Indian students were more internal.…”
Section: General Attitudes and Personality Variablesmentioning
confidence: 99%